PERANAN JAMINAN SOSIAL TENAGA KERJA DALAM PERWUJUDAN PEMBANGUNAN HUKUM TENAGA KERJA DI INDONESIA - Oktavia, Mita; Fatriani, Fenny (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Increasing the quality of production power and the level of welfare of the Indonesian people by focusing on labor is still ongoing, the government is implementing Law Number 3 of 1992 concerning Social Security for Workers with regulations regarding protection for workers in order to reduce the possibility of reduction to the loss of the ability to work and labor income due to the possibility of illness, disability, accidents and even death. Then, with the implementation of this social security program for workers, what is its role in the development of the complete workforce and the comprehensive development of Indonesian society as a form of embodiment of the development of labor law in Indonesia. The role of social security for workers in realizing the development of labor law in Indonesia is considered very crucial as mentioned in a normativejuridical research, the role of social security is very crucial, in order to achieve the objectives of this program, there must be increased understanding of the benefits of social security as well as expanding access for all workers, including workers in the informal sector. Apart from that, this program also acts as a manifestation of legal certainty to create stability in work relations which creates the realization of higher quality legal development in Indonesia.